Analysis of the Vegetation State of the Territory of Central Iraq Using Landsat Data - Pasko, Olga (2021)
Pasko, O., Staurskaya, N., Tokareva, O. S., Cabral, P., Lebedeva, N. A., & Majid, S. M. (2020). Analysis of the Vegetation State of the Territory of Central Iraq Using Landsat Data. In A. J. V., J. Subic, A. Grubor, & D. Privitera (Eds.), Handbook of Research on Agricultural Policy, Rural Development, and Entrepreneurship in Contemporary Economies (pp. 484-503). [chapter 24] (Handbook of Research on Agricultural Policy, Rural Development, and Entrepreneurship in Contemporary Economies). IGI Global. https://doi.org/10.4018/978-1-5225-9837-4.ch024